E3 Ligases Determine Ubiquitination Site and Conjugate Type by Enforcing Specificity on E2 Enzymes - David, Yael (American Society for Biochemistry and Molecular Biology, 2011)
Ubiquitin-conjugating enzymes (E2s) have a dominant role in determining which of the seven lysine residues of ubiquitin is used for polyubiquitination. Here we show that tethering of a substrate to an E2 enzyme in the absence of an E3 ubiquitin ligase is sufficient to promote its ubiquitination, whereas the type of the ubiquitin conjugates and the identity of the target lysine on the substrate are promiscuous. In contrast, when an E3 enzyme is introduced, a clear decision between mono- and polyubiquitination is made, and the conjugation type as well as the identity of the target lysine residue on the substrate becomes highly specific. These features of the E3 can be further regulated by auxiliary factors as exemplified by MDMX (Murine Double Minute X). In fact, we show that this interactor reconfigures MDM2-dependent ubiquitination of p53. Based on several model systems, we propose that although interaction with an E2 is sufficient to promote substrate ubiquitination the E3 molds the reaction into a specific, physiologically relevant protein modification.